2017
DOI: 10.1016/j.atherosclerosis.2017.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin treatment aggravates the glucocorticoid insufficiency associated with hypocholesterolemia in mice

Abstract: We have shown that simvastatin treatment aggravates the glucocorticoid insufficiency associated with hypocholesterolemia in mice. Our data suggest that (1) HMG-CoA reductase activity controls the adrenal steroidogenic capacity under hypocholesterolemic conditions and (2) imply that it might be important to monitor adrenal function in humans subjected to statin-based treatments aimed at achieving sub-physiological LDL-cholesterol levels, as these may potentially execute a negative impact on the glucocorticoid f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…The administration of simvastatin (20 mg/kg/day) via the oral route (mixed with the HFD) had no significant effect on blood lipid profile or body weight in mice. In accordance with our results, previous studies also reported non-significant effects of simvastatin on blood lipid profile and body weight in mice [ 51 , 52 ]. Even a dosage as high as 100 mg/kg of simvastatin had no significant effect on mice blood lipid profile, which could be due to a strong compensatory increase in HMG-CoA reductase that occurs in this species [ 53 ].…”
Section: Discussionsupporting
confidence: 93%
“…The administration of simvastatin (20 mg/kg/day) via the oral route (mixed with the HFD) had no significant effect on blood lipid profile or body weight in mice. In accordance with our results, previous studies also reported non-significant effects of simvastatin on blood lipid profile and body weight in mice [ 51 , 52 ]. Even a dosage as high as 100 mg/kg of simvastatin had no significant effect on mice blood lipid profile, which could be due to a strong compensatory increase in HMG-CoA reductase that occurs in this species [ 53 ].…”
Section: Discussionsupporting
confidence: 93%
“…As cholesterol is a precursor of glucocorticoid synthesis, AI may be present when serum cholesterol is lower than normal. An animal study demonstrated that in mice treated with high-dose simvastatin for 3 days, AI could be aggravated by their hypocholesterolemic condition [28]. Our results appear to support that hypothesis.…”
Section: Discussionsupporting
confidence: 84%
“…Knockout of apolipoprotein A-I (apoA-I), the main structural lipoprotein on HDL, reduced plasma HDL-C levels by ~74% and essentially depleted lipid droplets in the adrenal cortex. The production of corticosteroids under a basal or stress condition was also significantly reduced in apoA-I knockout mice ( 34 36 ). Like apoA-I knockout mice, Surf4 LKO mice display a similar reduction in plasma HDL cholesterol levels under fasting and non-fasting conditions.…”
Section: Discussionmentioning
confidence: 98%